Equine-Assisted Intervention in a child diagnosed with autism spectrum disorder: a case report - Cerino, Stefania; Borgi, Marta; Fiorentini, Ilaria; Correale, Cinzia; Lori, Alessia; Cirulli, Francesca (Rivista di psichiatria, 2016)
An increasing number of studies have shown the beneficial effects of both recreational and therapeutic interventions assisted by animals for children with Autism Spectrum Disorders (ASD). The observed effects are believed to be mainly due to the ability of some animals to positively engage people, thus potentially counteracting the social withdrawal characterizing these subjects. Here we report the case of a child with high-functioning autism who has been included in an Equine-Assisted Intervention (EAI) program for 2 years. In particular, the relationship with the animal was used to encourage child’s narrative abilities as a primary means of improving cognition and communication. This case represents a first attempt to theorize the role of human-animal interaction as an adjunct to classic therapeutic strategies in ASD. During the intervention, the child appeared to gradually abandon his attitude to avoid the contact with the present and to hide in imaginative past and future. We propose animal-assisted interventions as complementary approaches capable to facilitate the verbalization of the patient’s internal states and to promote psychological well-being through the development of a bond with the animal.